Congestive heart failure treated with peritoneal dialysis or hemodialysis: Typical patient profile and outcomes in real‐world setting. Issue 3 (1st November 2020) - Kunin, Margarita; Klempfner, Robert; Beckerman, Pazit; Rott, David; Dinour, Dganit
Abstract: Background: Peritoneal dialysis (PD) is increasingly used for the long‐term management of hypervolemic refractory congestive heart failure (CHF) patients, in particular when complicated by renal insufficiency. While PD has many advantages over hemodialysis (HD) in those patients, there is a controversy concerning survival superiority of PD compared with HD in this population. The aim of the study was to define typical patient profile and to compare outcomes of patients with CHF and renal failure treated with HD or PD. Methods: This retrospective cohort study enrolled CHF patients treated with chronic PD or HD between the years 2009‐2018. Information at dialysis initiation included age, gender, body weight, blood pressure, cause of renal disease, comorbidities, hospitalisations, echocardiographic and laboratory parameters. Survival was compared between PD and HD patients using a Kaplan‐Meier model and Cox regression analysis. Results: CHF patients treated with PD had significantly higher eGFR and lower systolic blood pressure compared with HD treated patients. Median survival time was 13.32 (7.08, 23.28) months in the PD group and 19.68 (9.48, 39.24) months in the HD group, P  = .013. After adjustment for confounders the mortality risk amongst PD and HD patients was not significantly different: adjusted HR for death in PD vs HD patients was 1.44, P  = .35 for 1‐ year and 1.69, P  = .10 for 2‐year mortality. Number of hospitalisations was similar in both groups. Conclusions: CHF patient profile was different in PD and HD. Two modalities were equally effective in the treatment of patients with CHF and renal failure considering different patient characteristics.